PENENTUAN LAPISAN TERKONTAMINASI RESIDU PUPUK MENGGUNAKAN METODA KELISTRIKAN PADA LAHAN PERTANIAN CEPAT PANEN - Ladaya A. Rakhmawati; Eleonora Agustine; Dini Fitriani; Mia Uswatun Hasanah (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2017)
Excessive fertilizer on farmland can increase or decrease mineral elements in the soil. If there is a change in the structure, then the land is a suspected of having the potential to experience contamination that affects the soil fertility. Cropping pattern in a farm area village